Retrospective review of spinal magnetic resonance images to determine the margin of safety for epidural analgesia in pediatric patients - Letofsky, Noah; Archibald, Dana; Ho, Anthony M.-H.; Navarro e Lima, Lais Helena [UNESP]; Lima, Rodrigo M. e; Quintão, Vinicius C.; Cançado, Fernando B.; Carlos, Ricardo V.; da Silva, Leopoldo M.; Bellicieri, Fernando N.; Silveira, Saullo Q.; Haghighat, Arvin; et al. (Elsevier, 2025)
BACKGROUND: Deeply sedated children cannot provide feedback if an epidural needle traumatizes the Spinal Cord (SC). Knowing relevant structure depths may, therefore, improve safety. We aimed to determine the epidural margin of safety, i.e., distances from the Ligamentum Flavum (LF) and from the dura mater to the SC in pediatric patients measured (i) Perpendicular to the SC and (ii) Parallel to the spinous process (to approximate needle trajectory). METHODS: Retrospective review of pediatric (0‒12 years-old) T2-weighted sagittal MRI spine scans without spinal pathology. Three investigators independently measured distances from the ventral edge of the LF, and from the ventral edge of the dura mater to the SC at T5/T6, T9/T10, and L1/L2. All measurements were taken perpendicular to the SC and parallel to the angle of the spinous process of the inferior vertebra. RESULTS: 111 MRI scans [52 females, 0.08‒12 (median 7) years-old] were analyzed. The conus medullaris was identified superior to the L1 vertebra in 47 scans, requiring L1/L2 measurement exclusion. When all ages were combined, the largest median (range) depth [dura-mater-SC = 4.87 (2.30‒10.30) mm, LF-SC = 8.10 (4.57‒12.53) mm, measured perpendicular to the SC; and dura-mater-SC = 8.20 (3.75‒19.57) mm; LF-SC = 13.40 (5.50‒39.77) mm, measured at the angle parallel to the inferior spinous process] was at T5/T6. CONCLUSION: Our results suggest that the margin of safety (dura-mater-SC distance and LF-SC distance) for performing epidurals in children may be greatest at the mid-thoracic spinal region. The measured ranges were very wide. Further studies are warranted to validate these findings in pediatric patients with other relevant "epidural placement" positions.